Clinical Implications of Plasma Epstein–Barr Virus DNA in Children and Adolescent Nasopharyngeal Carcinoma Patients Receiving Intensity-Modulated Radiotherapy - Qiu, Wenze; Lv, Xing; Guo, Xiang; Yuan, Yawei (Frontiers in Oncology, 2020)
Background Plasma Epstein-Barr virus (EBV) DNA has been determined as a prognostic factor in adult nasopharyngeal carcinoma (NPC) patients. This study was designed to evaluate the prognostic value of plasma pretreatment EBV DNA in children and adolescent NPC patients receiving intensity-modulated radiotherapy (IMRT). Methods Pretreatment EBV DNA was retrospectively assessed in 147 children with newly diagnosed, non-metastatic NPC. All patients were treated using IMRT. Receiver operating characteristic (ROC) curve was used to identify the optimal EBV DNA cut-off point. Prognostic value was examined using a multivariate Cox proportional hazards model. Results The median follow-up for the entire cohort was 58 months (range: 10-119 months), and the 5-year survival rates for all patients were as follows: overall survival (OS), 88.7%; locoregional relapse-free survival (LRRFS), 95.2%; distant metastasis-free survival (DMFS), 84.8%; and disease-free survival (DFS), 81.5%. For ROC curve analysis, the optimal cutoff value of pretreatment EBV DNA load for DFS was 40000 copies/mL. High plasma EBV DNA was significantly associated with poorer 5-year DMFS (70.6% vs. 89.1%, P=0.003) and DFS (63.9% vs. 86.9%, P<0.001). In multivariate analysis, high plasma EBV DNA was an independent predictor for DMFS and DFS. Conclusions Pretreatment EBV DNA level was a powerful prognostic discriminator for DMFS and DFS in children and adolescent NPC patients treated with IMRT.